2017
DOI: 10.3906/sag-1603-32
|View full text |Cite
|
Sign up to set email alerts
|

Differences in leptin, ghrelin, and glucagon-like peptide-1 levelsbetween religious fasting and normal fasting

Abstract: Background/aim: Leptin, ghrelin, and glucagon-like peptide-1 (GLP-1) affect hunger, satiety feelings, and food intake. We hypothesized that during Ramadan, if the brain knows that the body will be hungry until sunset, there may be differences between leptin, ghrelin, and GLP-1 levels in Ramadan and non-Ramadan fasting. Materials and methods:This study had two phases. In the first phase, the participants were asked to skip the dawn meal of Ramadan (suhur), so that 12 h of fasting could be achieved. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
1
0
1
Order By: Relevance
“…We report that GLP-1 concentrations decreased after RIF. Contrary to our results, other studies suggested insignificant changes in GLP-1 concentrations after RIF in females and males, suggesting that the hypothalamus most likely adapts to hunger-related to intentional fasting during Ramadan [19,46]. Furthermore, a non-significant decrease in GLP-1 occurs after RIF in obese females [19].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We report that GLP-1 concentrations decreased after RIF. Contrary to our results, other studies suggested insignificant changes in GLP-1 concentrations after RIF in females and males, suggesting that the hypothalamus most likely adapts to hunger-related to intentional fasting during Ramadan [19,46]. Furthermore, a non-significant decrease in GLP-1 occurs after RIF in obese females [19].…”
Section: Discussioncontrasting
confidence: 99%
“…Improvements in gut hormone concentration were observed after RIF. Our findings are in agreement with those of Çaklili et al who also reported that leptin concentrations increased following RIF, suggesting a role for leptin to satiety in RIF [46]. In contrast, leptin concentrations were decreased after 8 weeks of alternate-day fasting during weight loss in obese participants, which was interpreted as the brain becoming less sensitive to meal-generated satiety signals, leading to decreased leptin concentrations [45].…”
Section: Discussionsupporting
confidence: 93%